Performance Analysis of Narrowband-IoT Network for Smart Metering at 2100 MHz using Guard-Band Scheme in Urban Areas - Melinda Br Ginting; Fitrah Sadli Fahreza; Robin Sinurat (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2026)
The rapid development of the Internet of Things (IoT) increases the demand for communication technologies capable of supporting massive device connectivity with low power consumption and wide coverage. Narrowband Internet of Things (NB-IoT) is one of the cellular-based technologies designed to support large-scale IoT communication. This study aims to analyze the performance of an NB-IoT network operating at 2100 MHz using the guard-band deployment scheme for smart metering applications in an urban environment. The research method is conducted through network planning simulation by evaluating the performance parameters Reference Signal Received Power (RSRP) and Signal to Interference plus Noise Ratio (SINR). The simulation results show an average RSRP value of −112.52 dBm, indicating relatively weak signal strength within the service area. In addition, the average SINR value of 1 dB indicates low signal quality due to adjacent channel interference and propagation losses in urban environments. These results indicate that NB-IoT deployment at 2100 MHz with the guard-band scheme in urban areas faces signal-quality challenges, so that network optimization is required to improve the coverage and signal quality received by smart metering devices.